Functional Biomarkers: an Approach to Bridge Pharmacokinetics and Pharmacodynamics in Pediatric Clinical Trials - L. Kearns, Gregory; Artman, Michael (Current Pharmaceutical Design, 2015)
Over the past 30 years, much has been learned about the impact of development on drug disposition (i.e., pharmacokinetics). This is not true concerning drug action (i.e., pharmacodynamics). As a consequence, in clinical therapeutics and the drug development process, assumptions are often times made that a specific systemic drug exposure that is associated with desired drug action in adults will produce the same response in children. A review of the literature would suggest that this assumption may, in some cases, be an errant one. The relative paucity of information concerning developmental pharmacodynamics is associated with the challenge of assessing and quantitating drug response in vivo in infants and children. An approach to overcome these difficulties has been the evolution of biomarkers that are functional in nature in that they are capable of measuring drug response in both a time and age dependent fashion. The purpose of this review is to illustrate how functional biomarkers capable of assessing drug response/ effect in the developing child are developed and being evaluated for their clinical utility.
Keywords: pharmacokinetics